Pengaruh LDR Dan DER Terhadap Profitabilitas Perusahaan Perbankan Yang Terdaftar di Bursa Efek Indonesia Pada Tahun 2017-2022 - Risti Cahyani; Irfan Sophan Himawan (AKUNTANSI 45, 2024)
This study aims to examine the effect of Loan to Deposit Ratio (LDR) and Debt to Equity Ratio (DER) on Return on Asset (ROA) or Bank Profitability. This study uses time series data from financial reports and annual reports of banking companies listed on the IDX. After passing the purpose sampling stage, the appropriate sample used was 10 banking companies listed on the IDX. Data analysis is carried out quantitatively by conducting classical assumption tests which include normality tests, multicollinearity tests and heteroscedasticity tests. This study also uses multiple regression and hypothesis testing. The results showed that the research data were normally distributed, based on the normality test, multicollinearity test, heteroscedasticity test and autocorrelation test, there were no classical assumption deviations found. This indicates that the available data has met the requirements for using multiple linear regression models. The f test results show that the LDR and DER variables simultaneously have an significant effect on ROA. The t test results show that the LDR variable no effect on ROA. DER variable has a negative and significant effect on ROA.